Caractérisation phéno-morphologique de quelques lignées de fève (Vicia faba L.) sélectionnées et adaptées aux conditions de culture dans les régions arides en Tunisie - Dridi, Bouthaina Al Mohandes; Loumerem, Mohamed; Houimli, Samira Ibn Maaouia; Jabbes, Naouel; Tlahig, Samir (Afrika Focus, 2011)
The objective of the present study was to produce a pheno-morphological characterization of 13 faba bean lines selected by the Institute of Arid Regions from 42 local populations. The pheno-morphological variability of these lineages was observed and followed from planting through to seed maturity by biometric measurements and by qualitative evaluations on different plant parts. Morphological characteristics were described by using the UPOV (2000) descriptor. The analysis of results made it possible to distinguish between 2 groups based on precocity and hundred-seed weight. The first group was represented by line 8 which differs from others by the fact that it was the earliest and had the highest one hundred-seed weight. The second group was divided into 3 subgroups that differed in terms of plant vigour and productivity. The first subgroup was characterized by a lower number of flowers per raceme, a hundred-seed weight average ranging from 162.96 g to 165.24 g and a highest number of seeds per pod. This first subgroup contained the lines 5, 10, 11, 12 and 13. The second subgroup included lines 6, 7 and 9 which were the most homogenous on 50 % owering date, plant height and length of lea et. The latter subgroup included the lines 1, 2, 3 and 4, characterized by a highest number of pods per plant, number of stems per plant, and number of flowers per raceme. These lines should be preserved and valued for the varietal improvement programs of Vicia faba. Successive selection should be practiced until a more productive synthetic variety is obtained that is better adapted to the dry conditions of South Tunisia. Key words: Phenology, agromorphology, characterization, Vicia faba